ANALISIS DAMPAK PROGRAM BANTUAN PANGAN NON TUNAI DAERAH (BPNTD) TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT DI PROVINSI GORONTALO - Nurwahyuliningsih, Eka; Arsyad, Yolandika (Jurnal Studi Ilmu Politik, 2025)
This study aims to determine the effectiveness of the implementation of the Non-Cash Food Assistance Program in Gorontalo Province through an evaluation analysis of Chambers criteria and a rights-based approach. The study uses a qualitative approach with data collection methods through in-depth interviews, observations, and documentation studies. The data collection techniques use data reduction, data presentation, and drawing conclusions and verification. The research subjects were selected by purposive sampling, involving informants from the Beneficiary Group (KPM), Companions, Social Services, and related Policy Stakeholders. The results of the study showed that as a social program and policy, it can be said to have succeeded in reducing the expenditure of beneficiaries to meet food needs. However, the results of the analysis showed that there were several shortcomings or gaps in the implementation of the program, including duplicate data on beneficiaries, a minimal assistance monitoring system, a banking system that still cannot accommodate beneficiary data as a whole, and does not have a significant effect on changes in the economy of the poor. Thus, these findings can be used as evaluation material for local governments to be able to optimize similar programs in supporting sustainable improvements in community welfare.